Potential Health Implications of Medication Therapy Management Eligibility Criteria in the Patient Protection and Affordable Care Act Across Racial and Ethnic Groups - Wang, Junling (J Manag Care Spec Pharm, 2015)
BACKGROUND: The Medicare Prescription Drug, Improvement, and Modernization Act requires Part D plans to establish programs to provide medication therapy management (MTM) services starting from 2006. MTM services have been found to improve patient outcomes from pharmacotherapy, reduce emergency room visits and hospitalizations, and reduce health care costs in a cost-effective fashion. However, previous research found that non-Hispanic blacks (blacks) and Hispanics may be less likely to be eligible for MTM services than non-Hispanic whites (whites) among the Medicare population, according to current Medicare MTM eligibility criteria. This finding is because Medicare MTM eligibility criteria are predominantly based on medication use and costs, and blacks and Hispanics tend to use fewer prescription medications and incur lower prescription medication costs. The Patient Protection and Affordable Care Act (PPACA) laid out a set of MTM eligibility criteria for eligible entities to target patients for MTM services: “(1) take 4 or more prescribed medications …; (2) take any ‘high risk’ medications; (3) have 2 or more chronic diseases … or (4) have undergone a transition of care, or other factors … that are likely to create a high risk of medication-related problems.” OBJECTIVES: To (a) examine racial/ethnic disparities in meeting the eligibility criteria for MTM services in PPACA among the Medicare population and (b) determine whether there would be greater disparities in health and economic outcomes among MTM-ineligible than MTM-eligible groups. METHODS: This was a retrospective cross-sectional analysis of the Medicare Current Beneficiaries Survey (2007-2008). To determine medication characteristics, the U.S. Food and Drug Administration’s Electronic Orange Book was also used. Proportions of the population eligible for MTM services based on PPACA MTM eligibility criteria were compared across racial and ethnic groups using a chi-square test; a logistic regression model was used to adjust for population sociodemographic and health characteristics. Health and economic outcomes examined included health status (self-perceived good health status, number of chronic diseases, activities of daily living [ADLs], and instrumental activities of daily living [IADLs]), health services utilization and costs (physician visits, emergency room visits, and total health care costs), and medication use patterns (generic dispensing ratio). To determine difference in disparities across MTM eligibility categories, difference-in-differences regressions of various functional forms were employed, depending on the nature of the dependent variables. Interaction terms between the dummy variables for minority groups (e.g., blacks or Hispanics) and MTM eligibility were included to test whether disparity patterns varied between MTM-ineligible and MTM-eligible individuals. RESULTS: The sample consisted of 12,966 Medicare beneficiaries, of which 11,161 were white, 930 were black, and 875 were Hispanic. Of the study sample, 9,992 whites (86.4%), 825 blacks (86.3%), and 733 Hispanics (80.6%) were eligible for MTM. The difference between whites and Hispanics was significant (P < 0.050), and the difference between whites and blacks was not significant (P > 0.050). In multivariate analyses, significant disparity in eligibility for MTM services was found only between Hispanics and whites (odds ratio [OR] = 0.59; 95% CI = 0.43-0.82) but not between blacks and whites (OR = 0.78; 95% CI = 0.55-1.09). Disparities were greater among the MTM-ineligible than the MTM-eligible populations in self-perceived health status, ADLs, and IADLs for both blacks and Hispanics compared with whites. When analyzing the number of chronic conditions, the number and costs of physician visits, and total health care costs, the authors of this study found lower racial and ethnic disparities among the ineligible population than the eligible population. CONCLUSIONS: Hispanics are significantly less likely than whites to qualify for MTM among the Medicare population, according to MTM eligibility criteria stipulated in the PPACA. PPACA MTM eligibility criteria may aggravate existing racial and ethnic disparities in health status but may remediate racial and ethnic disparities in health services utilization. Alternative MTM eligibility criteria other than PPACA MTM eligibility criteria may be needed to improve the efficiency and equity of access to Medicare Part D MTM programs.